What Determines the Inclusion in a Sustainability Stock Index? A Panel Data Analysis for European Companies - Andreas Ziegler; Michael Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
This paper examines the determinants of the inclusion of European companies in the Dow Jones Sustainability World Index and the Dow Jones STOXX Sustainability Index. In doing so, the paper contributes to the micro-econometric literature analyzing the determinants and economic effects of sustainability performance in three respects: First, it examines a broad measure of corporate sustainability behavior and thus does not only apply narrow measures of environmental performance such as toxic releases which is common in other studies. Second, the paper examines the effect of internal assessment processes regarding corporate sustainability performance by an independent financial service institution. Finally, it analyzes the influence of unobserved heterogeneity in the framework of panel data models. The analysis shows that the probability for an inclusion in the sustainability indexes strongly decreases if a company does not respond to the written survey of the assessing institution. Furthermore, time invariant random effects and an autoregressive structure in the stochastic components are important factors. In contrast, a significant influence of past economic performance cannot be confirmed robustly.
Keywords: Q01; C23; G30; Q56; 330; Corporate sustainability performance; Sustainability stock indexes; Economic performance; Panel data; Probit models